Problem możliwości etyki zawodowej pośredników kredytu hipotecznego - Nowak, Arkadiusz Piotr (Annales. Etyka w Życiu Gospodarczym, 2020)
The purpose of this work is to present arguments that support the thesis about the need to formulate professional ethics for mortgage brokers. Due to the lack of a broader reflection on the professional ethics of this profession, a theoretical gap has arisen between general ethical thinking and the practice of ethical codes. Based on the literature, it was found that to formulate professional ethics, it is necessary to know the specifics of the work and to identify the specific ethical problems of the profession. These issues for mortgage brokers are described in this paper thanks to the use of the retrospective participant observation method. The conclusions of this study make it possible to recommend formulating the basics of professional ethics that refer to the value of professionalism, honesty, and responsibility.